The usage of Information and Communication Technology (ICT) for teaching and learning to improve the performance in Science subject Sekolah Kebangsaan Tanjung Latip / Jeniffer Nyawai - Nyawai, Jeniffer (2015)
The purpose of this study was to test the effectiveness of using electronic presentation application in the teaching and learning of science in primary schools. In the face of the world explosion of information, use of information technology and telecommunications (ICT) in teaching has become a necessity that cannot be denied its importance. The teachers were able to improve quality of teaching through the delivery of information to students, particularly using computer-based applications. Thus, this insult was conducted to determine to what extent the effective use of electronic presentation applications can improve learning outcomes student in Primary Science. Aspects that have been studied are the achievement levels of students, perceptions or electronic receipt and mastery level students to the concepts, terminology, and other phenomena - others in Science subject. The study was conducted using experimental methods, question and answer, and survey forms. Data were analyzed using methods appropriate to it. The sample consisted of 20 students in 5 elementary schools suburbs. The findings of this study demonstrate the effectiveness of using electronic presentation applications (ICT) in the teaching and learning of Primary Science. Perception is very encouraging students in the use of electronic presentations in learning. Teachers also support this method in implementing the teaching and learning process.